(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and subclinical characteristics of patients with Dengue Hemorrhagic Fever (DHF) treated at the Department of Infectious Diseases, Hoai Duc General Hospital, in 2023. Methods: A cross-sectional descriptive study was conducted on 346 inpatients diagnosed with DHF who met the inclusion criteria at the Department of Infectious Diseases, Hoai Duc General Hospital, from January to December 2023. Results: The mean age of the study population was 41,7± 14,6 years, with a predominance in the working-age group (under 40 years). The proportion of male patients (38.2%) was significantly lower than that of females (61.8%) (p < 0.05). Key clinical manifestations included high fever (94.2%), headache (97.1%), nausea (27.5%), vomiting (25.7%), and subcutaneous hemorrhage (34.1%). Complications such as pleural effusion and peritoneal effusion were recorded at 17.6% and 21.7%, respectively. Laboratory findings showed that leukopenia, thrombocytopenia, and hemoconcentration (increased hematocrit) were most pronounced during the critical phase. Furthermore, the prevalence of elevated liver enzymes increased progressively throughout the course of the disease. Conclusion: Dengue Hemorrhagic Fever is prevalent among the working-age population under 40. Fever and headache remain the most common symptoms, while gastrointestinal symptoms like nausea and vomiting are also frequent. Significant thrombocytopenia and increased hematocrit levels are closely associated with the severity of the disease.